Watershed studies at the Hubbard Brook Experimental Forest: Building on a long legacy of research with new approaches and sources of data. Issue 1 (24th January 2021) - Campbell, John L.; Rustad, Lindsey E.; Bailey, Scott W.; Bernhardt, Emily S.; Driscoll, Charles T.; Green, Mark B.; Groffman, Peter M.; Lovett, Gary M.; McDowell, William H.; McGuire, Kevin J.; Rosi, Emma J.
Abstract: The Hubbard Brook Experimental Forest (HBEF) was established in 1955 by the U.S. Department of Agriculture, Forest Service out of concerns about the effects of logging increasing flooding and erosion. To address this issue, within the HBEF hydrological and micrometeorological monitoring was initiated in small watersheds designated for harvesting experiments. The Hubbard Brook Ecosystem Study (HBES) originated in 1963, with the idea of using the small watershed approach to study element fluxes and cycling and the response of forest ecosystems to disturbances, such as forest management practices and air pollution. Early evidence of acid rain was documented at the HBEF and research by scientists at the site helped shape acid rain mitigation policies. New lines of investigation at the HBEF have built on the long legacy of watershed research resulting in a shift from comparing inputs and outputs and quantifying pools and fluxes to a more mechanistic understanding of ecosystem processes within watersheds. For example, hydropedological studies have shed light on linkages between hydrologic flow paths and soil development that provide valuable perspective for managing forests and understanding stream water quality. New high frequency in situ stream chemistry sensors are providing insights about extreme events and diurnal patterns that were indiscernible with traditional weekly sampling. Additionally, tools are being developed for visual and auditory data exploration and discovery by a broad audience. Given the unprecedented environmental change that is occurring, data from the small watersheds at the HBEF are more relevant now than ever and will continue to serve as a basis for sound environmental decision‐making. Abstract : The Hubbard Brook Experimental Forest was established in 1955 as a major center for hydrologic research in the northeastern US. Since that time, the scope of study has expanded to a collaborative, multidisciplinary research program that includes long‐term investigations of air, water, soils, plants, and animals. New lines of research continue to improve understanding of watershed response to disturbance to better inform land management decisions and policies.